A Study on The Scheduling Management Based on Advertisement - Raj, Taflin S. (Recent Research Reviews Journal, 2023)
In order to maintain, develop, manage, and control time and resource schedules for the completion of a project, policies and documentation must be established. The method of managing the timetable will monitor and control it throughout the project, which is a strategic advantage. The component of ad scheduling comes from the schedule management. Ad scheduling refers to the practice of restricting the advertising to run only on specific days of the week and periods of the day. By doing this, it is made sure that the adverts only appear on certain days or at certain hours. It is being utilized by Microsoft, Google, Facebook, and other companies. The use of schedule management for ad scheduling, as well as its uses and potential future applications, are covered in this study.